2016
DOI: 10.5114/reum.2016.64910
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of overlapping hidradenitis suppurativa and ankylosing spondylitis after the introduction of adalimumab

Abstract: Hidradenitis suppurativa is a chronic inflammatory disorder characterized by occlusion of the follicular pilosebaceous units of the skin. The treatment options are sometimes very limited and unpleasant odor and abundant drainage complicate the disease. Ankylosing spondylitis is a form of seronegative spondyloarthritis with predominantly axial but also peripheral joint involvement. Both of the conditions lower the patient’s quality of life and affect everyday activities.We describe a 39-year-old male patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…107,108 Early case reports and open-label trials demonstrated mixed results. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]109,110 In 4 larger placebo-controlled trials, adalimumab, 40 mg every other week, failed to achieve primary efficacy end points. [48][49][50] A subsequent phase 2 double-blinded trial randomized 154 patients to adalimumab 40 mg every other week, 40 mg weekly, or placebo.…”
Section: Tnf Inhibitorsmentioning
confidence: 99%
“…107,108 Early case reports and open-label trials demonstrated mixed results. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]109,110 In 4 larger placebo-controlled trials, adalimumab, 40 mg every other week, failed to achieve primary efficacy end points. [48][49][50] A subsequent phase 2 double-blinded trial randomized 154 patients to adalimumab 40 mg every other week, 40 mg weekly, or placebo.…”
Section: Tnf Inhibitorsmentioning
confidence: 99%
“…In the majority of studies, ADA was administered with the dosing regimen previously adopted for the treatment of psoriasis (80 mg at week 0, 40 mg at week 1 and then 40 mg every other week) [22]. The effects were satisfactory in accordance to both efficacy and safety of the treatment [21,[23][24][25][26][27][28][29][30][31][32][33]. In subsequent years, prospective studies based on larger groups and longer observation of patients were published.…”
Section: Adalimumabmentioning
confidence: 99%
“… 36–39 There are also cases of HS associated with ankylosing spondylitis, Crohn’s disease, pyoderma gangrenous, acne and psoriatic arthritis successfully treated with adalimumab. 40–46 Main articles regarding the use of adalimumab for the management of hidradenitis suppurativa in real-life setting are reported in Table 1 .…”
Section: Adalimumabmentioning
confidence: 99%